TOPICAL ISSUES FORMATION OF INCLUSIVE COMPETENCE OF FUTURE TEACHERS IN THE REPUBLIC OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article deals with the problems of preparing teachers for the provision of educational services to children with disabilities and special educational needs. Various theoretical approaches to the interpretation of the concepts of "training", "inclusive competence" are analyzed